In Situ Defect Engineering Route to Optimize the Cationic Redox Activity of Layered Double Hydroxide Nanosheet via Strong Electronic Coupling with Holey Substrate. Issue 1 (28th October 2021) - Jin, Xiaoyan; Lee, Taehun; Tamakloe, Wilson; Patil, Sharad B.; Soon, Aloysius; Kang, Yong‐Mook; Hwang, Seong‐Ju
Abstract: A defect engineering of inorganic solids garners great deal of research activities because of its high efficacy to optimize diverse energy‐related functionalities of nanostructured materials. In this study, a novel in situ defect engineering route to maximize electrocatalytic redox activity of inorganic nanosheet is developed by using holey nanostructured substrate with strong interfacial electronic coupling. Density functional theory calculations and in situ spectroscopic analyses confirm that efficient interfacial charge transfer takes place between holey TiN and Ni−Fe‐layered double hydroxide (LDH), leading to the feedback formation of nitrogen vacancies and a maximization of cation redox activity. The holey TiN−LDH nanohybrid is found to exhibit a superior functionality as an oxygen electrocatalyst and electrode for Li−O2 batteries compared to its non‐holey homologues. The great impact of hybridization‐driven vacancy introduction on the electrochemical performance originates from an efficient electrochemical activation of both Fe and Ni ions during electrocatalytic process, a reinforcement of interfacial electronic coupling, an increase in electrochemical active sites, and an improvement in electrocatalysis/charge‐transfer kinetics. Abstract : Here the development of a novel synthetic route to defect‐optimized high‐performance electrocatalyst via the hybridization‐driven in situ creation of crystal defects, is reported. The holey TiN−LDH nanohybrid with strong interfacial electronic coupling shows outstanding oxygen electrocatalytic activity for Li−O2 batteries, which is attributable to the feedback formation of nitrogen vacancies and the maximization of cation redox activity upon hybridization.